Perubahan parameter biologik jaringan kanker payudara mencit akibat pemberian isoflavon tempe - Siti Harnina Bintari; Siti Fatimah Moeis; Sarjadi Sarjadi (Jurnal Gizi Klinik Indonesia, 2013)
Background: Cancer is severe diseases caused by the changing of deoxyribonucleic acid (DNA) structure. Women who consume soy products have a lower risk for breast cancer, but it cannot be explained the kind of biomolecular aspects of soy product which gives this role.Objective: The aim of this research was to analyze the biological parameter changing of AgNORs, p53, Cas-3 and Bcl-2 in mouse (Mus musculus) C3H strain with breast cancer, as the impact of injecting isoflavone of tempeh.Method: The laboratory experimental research was done by posttest only randomized controlled group design. Subject of study were 18 mice (Mus musculus) C3H strain that were divided into 3 groups, each of which consists of 6 mice. The first group, the control (K), was not injected by isoflavone, while the second group (P1) and the third group (P2) were injected by 1.000 mg and 10.000 mg of tempeh isoflavone/kg diet/day, respectively. All groups were given the transplanted breast cancer cells. AgNORs parameters were selected to determine the level of proliferation and p53 parameters, Cas-3 and Bcl-2 to determine the appearance of apoptosis. Data were analyzed by using Manova and discriminant test for each parameter of cell proliferation.Results: Concentration of isoflavones supplementation with 1,000 and 10,000 mg / kgdiet / day gave effect to the reduction of AgNORs blots, expression of p53 and Cas-3 and increased expression of Bcl-2 in group P1 and P2 compared with control group, as indicated by high statistical values (p=0.000) between both groups or within the group. Results of discriminant test showed that Bcl-2 and AgNORs had dominant role in increased apoptosis and inhibition of cancer cell proliferation in experimental animal.Conclusion: Tempeh isoflavones can be used as a biological parameter change agent that marks the proliferation and apoptosis of mice (Mus musculus) C3H strain towards the normal cell cycle progression.